(untitled) (Research, Society and Development, 2021)
Occupational Health is characterized as a field of practices and strategic knowledge aimed at analyzing and intervening in work relationships that cause diseases and injuries. Interprofessional Education, in this context, proposes that undergraduate health students and professionals inserted in the services learn to cooperate collaboratively in the resolution of issues linked to work. This aims to report the experience of the collaborative practices developed by the scholarship holders of the Interprofessional Education Program in Health about prevention, promotion and education actions related to the health of workers incorporated into the Unified Health System. Exploratory, descriptive study, with a quantitative approach to the report experience of scholarship holders in the Pet / Health Interprofessionality project. From the prevention and health promotion actions carried out in the health units, the female gender was the predominant one; higher education was present in the team; a high rate of overweight and obesity was perceived in workers who claimed not to receive training frequently in the unit. Professional satisfaction was perceived in the work environment. They reported occasionally and frequently suffering pain in the neck, back and lumbar region; the level of pain reported was from uncomfortable to totally horrible. The practice of reflexology reflected in a decrease in the level of pain among workers. Work can be seen as a determining factor in the health-disease process of individuals and the community. Care for Workers’ Health aims to constitute a new field of action and intervention by the public health service network in Brazil.